Teknik Melukis Ubin Batu sebagai Model Edukasi Kewirausahaan Kreatif Berbasis Kearifan Lokal di Sanan Malang - Sumarwahyudi, Sumarwahyudi (Universitas Medan Area, 2025)
This community service program aims to develop painting skills on andesite stone tiles as a model of creative entrepreneurship education based on local wisdom in Sanan Village, Malang. The implementation method was carried out through several stages: preparation, socialization, technical training, mentoring using the peer-tutoring method, a mini exhibition, and follow-up in the form of establishing creative business groups. The results indicate an improvement in participants’ skills in preparing media, creating patterns, applying acrylic paint, and performing finishing techniques. Moreover, the program fostered entrepreneurial motivation and introduced alternative handicraft products with economic value to support the local creative economy. The main obstacles, namely uneven skills and limited design variations, were addressed through peer tutoring and the use of pattern references. This program generated positive impacts by enhancing artistic capacity, opening new economic opportunities, and strengthening local cultural identity.